Human Resource Management in Borderlands: Evolution, Digitalization, and Multidisciplinary Approaches - Eliyana Eliyana; Christiana Iman Kalis; Muhammad Irfani Hendri (Information Technology and Science (ITScience), 2026)
This study aims to analyze the development of Human Resource Management (HRM) research in borderland regions through a Systematic Literature Review (SLR) approach. The increasing complexity of cross border phenomena such as migration, digital transformation, artificial intelligence, data governance, global health systems, and sustainability requires an integrated synthesis of fragmented scholarly developments. The study follows the Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) guidelines, using Scopus as the primary database for publications from 2016 to 2026. A total of 49 articles were selected and analyzed using thematic, comparative, and contextual synthesis.The findings reveal that HRM research in borderlands remains predominantly anchored in Strategic Human Resource Management (SHRM), emphasizing organizational performance outcomes through variables such as employee engagement, leadership, organizational culture, training, and employee performance. Although emerging studies indicate a shift toward digital HRM, artificial intelligence governance, human rights based HRM, and cross border health and regulatory systems, these developments remain fragmented and lack theoretical integration. Dominant frameworks such as the Resource Based View, Institutional Theory, and Social Exchange Theory continue to be widely used; however, they are insufficient to fully explain the socio technical, ethical, and geopolitical complexity of borderland HRM contexts.The research gap identified in this study lies in the absence of an integrative and multidimensional framework that connects technological transformation, human centered governance, and cross border institutional dynamics within HRM scholarship. Existing studies tend to be siloed within organizational performance, technological adoption, or institutional regulation, without a unified conceptual synthesis.The novelty of this study lies in systematically synthesizing fragmented HRM literature in borderland contexts and proposing the need for a holistic, adaptive, and multidisciplinary HRM perspective that integrates digital technology, human rights, employee wellbeing, cultural diversity, regulatory systems, and global geopolitical dynamics. This study concludes that HRM in borderlands should be reconceptualized as an adaptive socio technical and institutional system rather than merely a performance driven organizational tool.